ニーオルスンにおける2011年春季集中観測期間の雲の特徴 - 西中, 規実子; 久慈, 誠; 矢吹, 正教; 塩原, 匡貴; Kimiko, Nishinaka; Makoto, Kuji; Masanori, Yabuki; Masataka, Shiobara (2013)
We investigated cloud characteristics during an intensive observation period in the springtime of the year 2011 at Ny-Ålesund using Micro Pulse LIDAR (MPL). We found that as total cloud fraction was larger and cloud base height was lower, the eccentricity tended to be larger, which indicates that there frequently appeared low-level cloud, that is, there dominated clouds like arctic stratus. 第4回極域科学シンポジウム 個別セッション：[OM] 気水圏 11月15日（金） 統計数理研究所 ３階セミナー室１（D305） conference object